2017
DOI: 10.1021/acsami.7b10749
|View full text |Cite
|
Sign up to set email alerts
|

Highly Stable Molybdenum Disulfide Protected Silicon Photocathodes for Photoelectrochemical Water Splitting

Abstract: Developing materials, interfaces, and devices with improved stability remains one of the key challenges in the field of photoelectrochemical water splitting. As a barrier to corrosion, molybdenum disulfide is a particularly attractive protection layer for photocathodes due to its inherent stability in acid, the low permeability of its basal planes, and the excellent hydrogen evolution reaction (HER) activity the MoS edge. Here, we demonstrate a stable silicon photocathode containing a protecting layer consisti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
64
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(70 citation statements)
references
References 26 publications
4
64
0
Order By: Relevance
“…12) and Fe 2 O 3 . 13,14 Previously explored photocathode materials include silicon, 15 InGaP 16 and Cu 2 O. 17 Unfortunately, the large bandgap or unsuitable band-edge position seriously limits the water-splitting efficiency of PECs fabricated using these materials.…”
Section: Introductionmentioning
confidence: 99%
“…12) and Fe 2 O 3 . 13,14 Previously explored photocathode materials include silicon, 15 InGaP 16 and Cu 2 O. 17 Unfortunately, the large bandgap or unsuitable band-edge position seriously limits the water-splitting efficiency of PECs fabricated using these materials.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, the TMDs/Si composite photoelectrodes have advantages of large specific surface areas, low material costs, and highly catalytic activities. Besides, the TMDs/Si configuration can effectively alleviate the poor kinetics for absorbing hydrogen ions (H + ) and photocorrosions on surface of p‐Si . Furthermore, the HER efficiency and stability in a solar‐driven PEC water splitting can be efficiently improved .…”
mentioning
confidence: 99%
“…Maier et al demonstrated relatively low, but stable photocurrent under the HER conditions for 60 days in 1 M HCl using a Pt-coated crystalline silicon (c-Si), [8] while a recent study by the Jaramillo group used a thin MoS 2 protected c-Si to show durability for up to 62 days. [9] While these longterm tests demonstrate steady-state operational stability of these devices, practical devices will be subjected to daily day/ night cycling, which will vary the potential at the semiconductor/protection layer/catalyst-electrolyte interface. Thus, there is a need to understand how this cycling will affect stability.…”
Section: Durability Testing Of Photoelectrochemical Hydrogen Productimentioning
confidence: 99%